Wage-hours contracts, overtime working and premium pay - Robert A. Hart; Yue Ma (Institute for the Study of Labor (IZA), 2008)
This paper offers a contract-based theory to explain the determination of standard hours, overtime hours and overtime premium pay. We expand on the wage contract literature that emphasises the role of firm-specific human capital and that explores problems of contract efficiency in the face of information asymmetries between the firm and the worker. We first explore a simple wage-hours contract without overtime and show that incorporating hours into the contract may itself produce efficiency gains. We then show how the introduction of overtime hours, remunerated at premium rates, can further improve contract efficiency. Our modelling outcomes in respect of the relationship between the overtime premium and the standard wage rate relate closely to earlier developments in hedonic wage theory. Throughout, we emphasise the intuitive reasoning behind the theory and we also supply relevant empirical evidence. Mathematical derivations are provided in an appendix.
urn:nbn:de:101:1-20081126712
Keywords: J41; 330; Wage-hours contracts; overtime; premium pay; specific human capital; asymmetric information; Arbeitszeit; Überstunden; Vergütungssystem; Arbeitsvertrag; Vertragstheorie; Humankapital; Asymmetrische Information; Theorie; Großbritannien